Buya Hamka's Islamic Thought and Its Relevance to Islamic Education - Mustaminah (Maklumat: Journal of Da'wah and Islamic Studies, 2023)
The current education system is the result of the efforts and dedication of educational figures in the past, such as Buya Hamka, who made important contributions to the formation of the foundation and values of education. Buya Hamka considered education not only as a tool for the advancement of science, but also as a basis for human success in various aspects of life. The principles of courage and freedom of thought emphasized show that education should form individuals who are courageous and have intellectual freedom. Understanding the views of educational figures, including Buya Hamka, rewards their role in shaping the current education system, becoming a source of inspiration to continue to improve and develop education in the future. The purpose of this study is to understand the rationale according to Hamka, know the purpose of education according to Hamka, and assess the relevance of education to Islamic religious education. This research uses qualitative methods with literature review, collecting data from books by Buya Hamka and other papers that discuss it. The results showed that Buya Hamka's thoughts on Islamic education focused on maximum efforts in personal formation and strengthening.